2020
DOI: 10.3390/app10217464
|View full text |Cite
|
Sign up to set email alerts
|

Expert System for Mandibular Condyle Detection and Osteoarthritis Classification in Panoramic Imaging Using R-CNN and CNN

Abstract: Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative condition of the TMJ led by a pathological tissue response of the joint under mechanical loading. It is characterized by the progressive destruction of the internal surfaces of the joint, which can result in debilitating pain and joint noise. Panoramic imaging can be used as a basic screening tool with thorough clinical examination in diagnosing TMJ OA. This paper proposes an algorithm that can extract the condylar region and determine its abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…Based on this result, AI performed best for TMJOA diagnosis on OPG when indeterminate OA was omitted during training and verification. The pilot study showed similar accuracy (0.77-0.84) with various AI models when indeterminate OA was omitted 13 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on this result, AI performed best for TMJOA diagnosis on OPG when indeterminate OA was omitted during training and verification. The pilot study showed similar accuracy (0.77-0.84) with various AI models when indeterminate OA was omitted 13 .…”
Section: Discussionmentioning
confidence: 61%
“…Various studies have applied AI algorithms to read OPG for clinical conditions such as tooth segmentation 6 , age estimation 7 , third molar and inferior alveolar nerve detection 8 , cysts and tumors of the jaw 9 , osteoporosis 10 , and maxillary sinusitis 11 . However, there are few AI studies on TMJOA diagnosis; one study that used CBCT and one study based on OPG have been reported 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on this result, AI performs best for TMJOA diagnosis on OPG when indeterminate OA was omitted during it trained and veri ed. The pilot study showed similar accuracy (0.77-0.84) with various AI models when indeterminate OA was omitted 13 .…”
Section: Discussionmentioning
confidence: 61%
“…In this study, AI was designed to extract ROI from OPG by an algorithm based on object detection technique. The average precision of mandibular condyle detection was reported as 99.4% on right side and 100% on left side in previous study 13 . The ROI extracted automatically for the study covers mandibular condyle, articular fossa and eminence, which is very important because TMJOA is not de ned only by bony change of the condyle.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation